2010
DOI: 10.1007/s12157-009-0144-3
|View full text |Cite
|
Sign up to set email alerts
|

La thrombose veineuse portale de l’adulte: à propos de 28 cas

Abstract: But : Préciser le profil épidémioclinique, étiologique et thérapeutique des thromboses veineuses portales au Maroc. Matériel et méthode : Étude rétrospective de 28 cas de thrombose portale colligés dans le service de gastroentéro-logie du CHU Mohammed-VI de Marrakech, sur une période de quatre ans entre janvier 2004 et décembre 2008.Résultats : Les dossiers de 20 femmes et huit hommes, de 40 ans de moyenne d'âge, ont été étudiés. Les signes cliniques révélateurs étaient représentés par des douleurs abdominales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Contrary to what is described in the literature, in our series, thrombosis was complete in 71.4% of cases. The Moroccan study found similar rates (80%) of complete thrombosis [4].…”
Section: Analysis Of Cross-sectional Studies Of Patients With Cirrhosis Shows An Overallmentioning
confidence: 66%
See 1 more Smart Citation
“…Contrary to what is described in the literature, in our series, thrombosis was complete in 71.4% of cases. The Moroccan study found similar rates (80%) of complete thrombosis [4].…”
Section: Analysis Of Cross-sectional Studies Of Patients With Cirrhosis Shows An Overallmentioning
confidence: 66%
“…In our series, a local cause was present in 93% of cases. A Moroccan study conducted between 2004 and 2008 found a local cause in 75% of cases [4].…”
Section: Discussionmentioning
confidence: 99%